Pemanfaatan Media Digital dalam Pembelajaran Deforestasi pada Mata Pelajaran IPS di Sekolah Menengah Pertama - Isvina Agisni Idrizi; Muhammad Hifdil Islam; Nining Winarsih (Universitas Muhammadiyah Mataram, 2026)
This study aims to examine the utilization of digital media in teaching deforestation topics in Social Studies and its role in enhancing students’ understanding, environmental awareness, and critical thinking skills. A qualitative approach with a case study design was employed. The participants consisted of 2 Social Studies teachers and 2 VII-grade students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that digital media, particularly images and videos, facilitate students’ understanding of the causes, impacts, and mitigation efforts of deforestation in a more engaging and accessible manner. Furthermore, the use of digital media increases students’ attention, participation, and engagement during the learning process. These findings suggest that digital media can serve as an effective and contextual instructional tool in Social Studies education, fostering character development and strengthening students’ critical thinking skills